Inflammatory Myofibroblastic Tumors of the Female Genital Tract Are Under-recognized: A Low Threshold for ALK Immunohistochemistry Is Required. (October 2017) - Pickett, Justine L.; Chou, Angela; Andrici, Juliana A.; Clarkson, Adele; Sioson, Loretta; Sheen, Amy; Reagh, Jessica; Najdawi, Fedaa; Kim, Yoomee; Riley, Denise; Maidens, Jayne; Nevell, David; et al.
Abstract : Inflammatory myofibroblastic tumor (IMT) of the female genital tract is under-recognized. We investigated the prevalence of ALK-positive IMT in lesions previously diagnosed as gynecologic smooth muscle tumors. Immunohistochemistry (IHC) for ALK was performed on tissue microarrays of unselected tumors resected from 2009 to 2013. Three of 1176 (0.26%) "leiomyomas" and 1 of 44 (2.3%) "leiomyosarcomas" were ALK IHC positive, confirmed translocated by fluorescence in situ hybridization (FISH) and therefore more appropriately classified as IMT. On review significant areas of all 4 tumors closely mimicked smooth muscle tumors morphologically, but all showed at least subtle/focal features suggesting IMT. Recognizing that the distinction between IMT and leiomyoma/leiomyosarcoma can be subtle, we then reviewed 1 hematoxylin and eosin slide from each patient undergoing surgery for "leiomyoma" from 2014 to 2017 and selected cases for ALK IHC with a low threshold. Of these, 30 of 571 (5.3%) underwent IHC. Two were confirmed to be IHC positive and FISH rearranged. Of the 6 IMTs, only 1 tumor with a previous diagnosis of leiomyosarcoma, an infiltrative margin and equivocal necrosis, metastasized. Of note it demonstrated a less aggressive clinical course compared with most metastatic leiomyosarcomas (alive with disease at 6 y). The patient was subsequently offered crizotinib to which she responded rapidly. In conclusion, IMTs may closely mimic gynecologic smooth muscle tumors. IMTs account for at least 5 of 1747 (0.3%) tumors previously diagnosed as leiomyoma and 1 of 44 (2.3%) as leiomyosarcoma. These tumors may be recognized prospectively with awareness of subtle/focal histologic clues, coupled with a low threshold for ALK IHC.